Microleakage difference between total-etch and self-etch bonding in bulk fill packable composite restoration after carbonic acid immersion - Widya Saraswati; Dian Pramita Ayu Kumalasari; Adioro Soetojo (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Bulk fill packable composite that can be applied to a depth of 4mm in cavities is widely used in posterior teeth restoration. Unfortunately, this composite is subject to potential microleakage which occurs due to erosion resulting from the consumption of carbonated drinks containing carbonic acid. Nevertheless, microleakage can be reduced by bonding applications the etch technique of which is divided into two forms; self-etch bonding and total-etch bonding. Purpose: This study aims to determine the difference in microleakage between total-etch and self-etch bonding in bulk fill packable composite following carbonic acid immersion. Methods: This study constitutes experimental laboratory research utilizing 28 incisors bovine teeth which were cleaned, immersed in 0.01% NaCl, and randomly divided into four groups. The cervical area of the teeth of all groups were prepared through the creation of cylindrical shapes 2mm in diameter and 3 mm deep. Groups I and III used total-etch bonding, while groups II and IV used self-etch bonding. Groups III and IV were control groups, whereas groups I and II were treatment groups (immersed in carbonic acid) for 24 hours. Thermocycling was carried out in all groups which were subsequently immersed in 1% methylene blue for 24 hours after which the teeth were cut in a buccolingual direction using a diamond disc wheel. Microleakage was subsequently evaluated by calculating the amount of methylene blue passing between the restoration wall and cavity using a Stereomicroscope and scanning electron microscope (SEM). The data was then analyzed using Kruskal Wallis and Mann Whitney U tests. Results: There was a significant difference between the control groups and treatment groups (p<0.05). The microleakage in Group 2 was higher than that of other groups. Conclusion: The microleakage of total-etch bonding was lower than self-etch bonding in bulk fill packable composite after carbonic acid immersion.